Using Scrabble Word Game to Improve Students' Vocabulary Mastery - Khairun Niswa; Indi Sabila (English Teaching and Linguistics Journal (ETLiJ), 2023)
This research was conducted using the Classroom Action Research method, which was conducted to describe the application of the scrabble game to improve the vocabulary of the first graders of SMPN1 Bahorok. Classroom Action Research Method (CAR) is a method used to solve students' problems in learning English, especially vocabulary. The Kemmis and McTaggart design used in this study, which consisted of four stages; planning; action; observation; and reflection on each cycle. To support the research results, two types of data were collected; Qualitative data obtained from observations, teacher and student interviews. As for quantitative data, data from tests; pre-test and post-test. Furthermore, the data were analyzed descriptively and statistical analysis to determine the final result of the application of the scrabble game on the student learning process in Classroom Action Research (CAR). The results of this study indicate that the use of scrabble games for vocabulary learning in class I SMPN 1 Bahorok is said to be effective and can help students increase vocabulary. Student responses indicate that students are interested in learning English because students find the activity interesting. Simultaneously, student achievement obtained from the pre-test and post-test showed a significant increase. The mean score of the pre-test students was 56.42 while the average score of the post-test students was 74.82, an increase of 18.4. From these results, it can be concluded that teaching vocabulary using scrabble games in grade I SMPN1 Bahorok is effective and can increase students' vocabulary